Private international law : a case study - Govindaraj, V. C. (New Delhi : Oxford University Press, 2019)
Private international law or conflict of laws deals with cases that have cross-border implications. The question involved is which state has the jurisdiction to decide a case involving complex inter-territorial issues. Judges of the superior courts in India lean heavily on English case-law and on the views of renowned English jurists, like Dicey and Cheshire, in deciding cases on conflict of laws. This text deals with cases that call for comment in the three main areas of the subject, namely the law of obligations, the law of persons, and the law of property, besides cases that call for comment in respect of foreign judgments and foreign arbitral awards, as also the law relating to procedure.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 9, 2019).
Keywords: Conflict of laws; Law; Jurisprudence & general issues